The Impact of Subsyndromal Bipolar Symptoms on Patient’s Functionality and Quality of Life - Grunze, Heinz; Born, Christoph (Frontiers in Psychiatry, 2020)
Subsyndromal symptoms have rarely been in the focus of bipolar research. This may be, in part, due to the fact that there is neither a uniform definition nor do they constitute an indication of regulatory and commercial interest. Nevertheless, they do have a decisive impact on the long- term course of bipolar disorder, and the degree of functionality and quality of life is more likely determined by their presence or absence than by acute episodes. Summarizing the literature an estimated 20-50% of patients suffer inter-episodically or chronically from subsyndromal bipolar disorder. The most prominent symptoms that interfere with functionality are subsyndromal depression, disturbances of sleep and perceived cognitive impairment, whereas anxiety negatively impacts on quality of life. In the absence of evidence based pharmacological treatments for subsyndromal bipolar disorder, clinical practice adopts guidelines designed for treatment-resistant full-blown episodes of bipolar disorder, supplemented by cognitive-behavioural, family focused or social-rhythm based psychotherapies.